(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
Sixty-one species assignable to 31 genera of Late Carboniferous and Early Permian fusulinoideans were distinguished from the Hadim area, central Taurides, Turkey. They are biostratigraphically divided into eleven zones in ascending order: Protriticites variabilis, Montiparus umbonoplicatus and Schwageriniformis schwageriniformis zones in the Kasimovian; the Jigulites aff. formosus, Daixina asiatica and Rugosofusulina sp. A zones in the Gzhelian; Paraschwagerina sp. and Dutkevichia complicata zones in the Asselian; Paraschwagerina pseudomira and Robustoschwagerina nucleolata zones in the Sakmarian; and the Dunbarula? sp. zone of possible Artinskian age. Basal Kasimovian strata, Kasimovian-Gzhelian boundary strata and lower Asselian strata are missing due to erosion and/or non-deposition on the basis of faunal analysis of these fusulinoideans. Among the described species, newly proposed herein are Eoparafusulina brevis, Robustoschwagerina hadimensis, Pseudoschwagerina globosa, and Pseudoschwagerina ozguli. E. brevis is thought to be phylogenetically related to the Monodiexodina lineage along with E. ferganica. R. hadimensis represents a small form of the genus. P. globosa showing Sphaeroschwagerina-like appearance has a distinct Triticites-type juvenarium suggesting a specialized descendant derived from an Asselian Pseudoschwagerina. P. ozguli is distinguished from most of known species of Pseudoschwagerina by its smaller test and its occurrence from the Sakmarian.